2020
DOI: 10.3389/fncel.2020.600758
|View full text |Cite
|
Sign up to set email alerts
|

Store-Operated Calcium Channels in Physiological and Pathological States of the Nervous System

Abstract: Store-operated calcium channels (SOCs) are widely expressed in excitatory and non-excitatory cells where they mediate significant store-operated calcium entry (SOCE), an important pathway for calcium signaling throughout the body. While the activity of SOCs has been well studied in non-excitable cells, attention has turned to their role in neurons and glia in recent years. In particular, the role of SOCs in the nervous system has been extensively investigated, with links to their dysregulation found in a wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 167 publications
(275 reference statements)
0
19
0
Order By: Relevance
“…SOCE plays an important role in the nerve terminals where α-syn is present in high concentrations (77). Upon Ca 2+ depletion of ER, Ca 2+ -selective store-operated channels (SOCs) are assembled by interaction between ER Ca 2+ -sensing STIM1/2 proteins and plasma membrane-associated ORAI1/2/3 proteins, which together form the PM Ca 2+ release-activated Ca 2+ (CRAC) channels, thereby allowing restoration of ER Ca 2+ stores by influx from the extracellular space (78). In addition to ORAI proteins, the transient receptor potential canonical channels (TRPC) have also been suggested to participate in CRAC channel formation (78,79).…”
Section: Ryrmentioning
confidence: 99%
See 1 more Smart Citation
“…SOCE plays an important role in the nerve terminals where α-syn is present in high concentrations (77). Upon Ca 2+ depletion of ER, Ca 2+ -selective store-operated channels (SOCs) are assembled by interaction between ER Ca 2+ -sensing STIM1/2 proteins and plasma membrane-associated ORAI1/2/3 proteins, which together form the PM Ca 2+ release-activated Ca 2+ (CRAC) channels, thereby allowing restoration of ER Ca 2+ stores by influx from the extracellular space (78). In addition to ORAI proteins, the transient receptor potential canonical channels (TRPC) have also been suggested to participate in CRAC channel formation (78,79).…”
Section: Ryrmentioning
confidence: 99%
“…By inducing Ca 2+ influx into the cytoplasm and ER as a consequence of ER Ca 2+ depletion, SOCE plays an important role in maintaining neuronal Ca 2+ homeostasis, and SOCE has been linked to a multitude of biological processes, including transcription, exocytosis, and metabolism (78). The α-syn aggregate dependent activation of SERCA that increases ER Ca 2+ levels holds potential for disturbing SOCE (21).…”
Section: Ryrmentioning
confidence: 99%
“…The role of SOCs in abnormal Ca 2+ handling in DMD has been investigated, and targeting of SOCs to restore Ca 2+ homeostasis for DMD therapies has been discussed previously [ 18 , 54 ]. While Orai1 and STIM1 are major components of SOCs, other Ca 2+ channels, such as TRPC1, TRPV, and TRPM7, also contribute to SOC activity [ 55 , 56 ]. In this study, siRNA-mediated knockdown experiments revealed that Orai1 and STIM1 are the most prominent candidates for SOCs regulating Ca 2+ overload in DMD.…”
Section: Discussionmentioning
confidence: 99%
“…However, different cell distribution as well as potentially different functions of STIM1 and STIM2 may also be contributing factors. For example, STIM2 has been implicated in regulating basal neuronal Ca 2+ levels, whereas it has been suggested that STIM1 is an important regulator of mGluR1-mediated Ca 2+ signaling ( Zhang and Hu, 2020 ). Similar to the cardiomyocyte studies, targeting the balance between STIM1 and STIM2 levels should be explored in more detail.…”
Section: Stim/orai In Neurodegenerationmentioning
confidence: 99%